Analgesia in donkeys: the state of the art (Research, Society and Development, 2020)
Throughout evolution, both in animals and humans, pain worked as a consequence of the survival instinct, as it has a protective function in the body, important for physical integrity. Its intensity varies according to the pathology and severity of the tissue injury, as well as the pain threshold of each species, yet individual peculiarities should be considered. It is known that donkeys, when compared to horses, show more subtle or almost imperceptible signs of pain, the most observed signs being apathy, lack of appetite, lameness and reluctance to move, behaviors that are not always related to pain and that some of these are common in several illnesses. The literature on donkey pain control therapy is also scarce, and most protocols are followed using those indicated for horses, although differences between physiology, pharmacokinetics and drug metabolism have already been proven. Therapies for pain control can be done alone, or through multimodal therapies, using a combination of drugs from different classes and analgesic techniques. The main drugs described for analgesia in donkeys in different pathologies are phenylbutazone, flunixin, butorphanol and detomidine. Although often not as important and focused as horses, more research with donkeys is necessary, especially with regard to their behavior, pain management, and appropriate therapeutic dosages, thus helping in well-being, quality of life and workforce in assisting human development. This review article seeks to elucidate fundamentals about pain and promotion of analgesia in donkeys.